Diskriminator Perilaku UMKM sebagai Debitur Kredit pada PT Permodalan Nasional Madani Mekaar Cabang Ajung - Kholifatan Nisa; Hari Sukarno; Nurul Setianingrum (Jurnal Syntax Admiration, 2024)
The objectives of this study are: 1) To examine and analyze the role of cultural factors as differentiators of loyal debtors and debtors who have the potential to move. 2) To examine and analyze the role of social factors as differentiators of loyal debtors and potentially moving debtors. The research approach used in this study is quantitative research with discriminant analysis research methods. Discriminant analysis is a data analysis technique where the specific variable (variable Y) is categorical data (nominal) while the independent variable (variable X) is ordinal data. As a result of the analysis, it can be concluded that the debtor discriminator that is able to distinguish loyal debtors and those who have the potential to move is the Bud variable. So, if the debtor does not understand about Sos, Pri, and Psi, then it does not matter because the one who is able to discriminate against the three categories of debtors is Bud.